Acetaminophen intake and risk of asthma, hay fever and eczema in early adolescence - Emilija Vlaski; Stavric, Katerina; Isjanovska, Rozalinda; Seckova, Lidija; Kimovska, Milica (My University, 2007)
A positive association between acetaminophen intake and allergic diseases has recently been reported in developed countries with impaired oxidant/antioxidant balance and promotion of atopy as proposed underlying mechanisms. The aim of the study was to explore the relationship between acetaminophen intake and asthma, hay fever, and eczema in The Republic of Macedonia as a country with acetaminophen intake not physician-controlled, high passive smoke exposure and dietary antioxidant intake, and moderately low prevalence of allergic diseases. Self-reported data obtained through the standardized International Study of Asthma and Allergies in Childhood Phase Three written questionnaires of 3026 adolescents aged 13/14 years from randomly selected schools in Skopje, the capital of Macedonia, were used. The frequency of current acetaminophen intake--both unadjusted and adjusted for confounding factors--was correlated to current and ever-diagnosed asthma, hay fever and eczema by odds ratios (OR, 95% CI) in binary logistic regression. Use of acetaminophen at least once monthly increased the risk of current wheeze (adjusted OR 2.04, 1.31-3.20 p = 0.002), asthma 'ever' (adjusted OR 2.77, 1.06-7.26 p=0.039), current allergic rhinoconjunctivitis (adjusted OR 2.95, 1.79-4.88 p=0.000) and hay fever 'ever' (adjusted OR 2.25, 1.36-3.70 p=0.002). A significant association between frequent acetaminophen intake and atopic eczema and also between infrequent acetaminophen intake and investigated allergic diseases was not established. The findings suggest an increased risk of asthma and hay fever, but not atopic eczema associated with frequent acetaminophen use in a developing country.
Keywords: acetaminophen; adolescents; asthma; atopic eczema; hay fever